Range expansion of the tracheal mite Acarapis woodi (Acari: Tarsonemidae) among Japanese honey bee, Apis cerana japonica, in Japan - Maeda, Taro; Sakamoto, Yoshiko (Experimental & applied acarology, 2020)
Acarapis woodi , a parasitic mite of honey bees, was first detected in Japan in 2010. Infestation was mostly observed in the Japanese honey bee ( Apis cerana japonica ) and was rare in the European honey bee ( Apis mellifera ). By 2014, the mites had spread throughout central and eastern Japan. In the current study, we investigated the subsequent expansion of the mite to western Japan. Our research revealed that the mites were distributed across most of Japan by 2018, except for Wakayama and Kochi prefectures. Many small remote islands more than 20 km away from mainland Japan are still free of A. woodi , but bees on some of these islands were infested. About 40% of colonies of the Japanese honey bee in Japan were infested by the mites, and average mite prevalence of the infested colonies was about 50% during the 6-year study. There was no trend of decline in the infested colony proportion or in the mite prevalence. In addition, the observation of Japanese honey bee colonies by hobby beekeepers for two signs of mite infestation, K-wing and crawling bees, was an effective means for estimating infestation by tracheal mites.